Tinnitus and vertigo in chronic kidney disease patients: an observational study at tertiary care centre - Rosario, David; Kodalkar, Nikhil; Sequeira, Anitha (International Journal of Research in Medical Sciences, 2022)
Background: Chronic kidney disease is characterized by the progressive and irreversible loss of kidney function over a period of months and years. Due to antigenic similarity, the cochlea and kidney have similar physiological mechanisms namely active transport of fluid and electrolytes achieved by stria vascularis in the cochlea and glomeruli in the kidney. Objective was to inspect the relation between hemodialysis and development of tinnitus and vertigo in CKD patients. Methods: Prospective observational study conducted at Srinivas Institute of medical science, Mangalore, 88 patients were enrolled in this study. Results: Out of 88 patients studied 09 patients (10.22%) complain of tinnitus, 12 patients (13.63%) complain of vertigo, 48 patients (54.54%) had both tinnitus and vertigo, and the remaining 19 patients (21.59%) didn’t develop any tinnitus or vertigo symptoms. The pure tone audiometry results in these individuals were indicative of inner ear pathology. The statistical analysis was done using SPSS 22. Conclusions: Vertigo and tinnitus are common with haemodialysis in patients with chronic kidney disease as 78.40% were affected with either tinnitus or vertigo or with both.